ANALYSIS OF TRANSPARENCY OF THE MECHANISM FOR DISTRIBUTING GRIEF SOCIAL ASSISTANCE FUNDS AT THE NORTH MINAHASA REGENCY SOCIAL SERVICE - Yetty Marni Pangemanan; Sisca B. Kairupan; Steven V. Tarore (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the level of transparency in the social assistance fund distribution mechanism at the North Minahasa Regency Social Service and identify factors influencing this low level of transparency. This study uses a qualitative approach with a case study. Data were collected through in-depth interviews with service officials, village officials, aid recipients, and community leaders, supplemented by a documentary study of regulations and official reports. The research findings indicate that transparency in the distribution of bereavement aid remains at a low level. Procedurally, the mechanism is reactive and relies heavily on recommendations from village heads without substantive verification of the recipients' economic conditions. The informational dimension has not been realized due to the lack of proactive publication of recipient lists, selection criteria, and distribution flows through media easily accessible to the public. Meanwhile, the accountability dimension is weak due to the lack of institutionalized community participation, the absence of structured complaint channels, and formal oversight that only focuses on administrative-financial compliance. This low level of transparency is influenced by three mutually reinforcing factors: (1) technical-managerial limitations in the form of data fragmentation and budget cycle pressures, (2) socio-cultural norms that prioritize apparent harmony and avoid conflict, and (3) regional regulations that do not explicitly bind transparency as a legal obligation.